Effect of Circadian Clock and Light–Dark Cycles in Onchidium reevesii: Possible Implications for Long-Term Memory - Xu, Guolyu (Genes (Basel), 2019)
The sea slug Onchidium reevesii inhabits the intertidal zone, which is characterized by a changeable environment. Although the circadian modulation of long-term memory (LTM) is well documented, the interaction of the circadian clock with light–dark masking in LTM of intertidal animals is not well understood. We characterized the LTM of Onchidium and tested the expression levels of related genes under a light–dark (LD) cycle and constant darkness (i.e., dark–dark, or DD) cycle. Results indicated that both learning behavior and LTM show differences between circadian time (CT) 10 and zeitgeber time (ZT) 10. In LD, the cry1 gene expressed irregularly, and per2 expression displayed a daily pattern and a peak expression level at ZT 18. OnCREB1 (only in LD conditions) and per2 transcripts cycled in phase with each other. In DD, the cry1 gene had its peak expression at CT 10, and per2 expressed its peak level at CT 18. OnCREB1 had two peak expression levels at ZT 10 or ZT 18 which correspond to the time node of peaks in cry1 and per2, respectively. The obtained results provide an LTM pattern that is different from other model species of the intertidal zone. We conclude that the daily transcriptional oscillations of Onchidium for LTM were affected by circadian rhythms and LD cycle masking.